Géographie des artistes dans les régions urbaines en Belgique - Tatiana Debroux (Belgeo)
This paper presents the spatial distribution of artists in the different urban areas of Belgium, with regard to the issue of links between culture and urban development. The role of creators in cities’ economic processes, though often mentioned, is generally considered in simplistic terms. However, studies have shown that the geography of artists is a significant and pertinent contribution upon which an analysis of the relations between cultural activities and contemporary urban dynamics can be built.Three dimensions are taken into account: several scales of spatial analysis, distinction between artistic disciplines, and temporal evolution of artists’ presence. These three dimensions allow us to better understand the features and differences peculiar to the territories and to imagine new paths for a deepened comprehension of the logics and issues related to artists’ distribution, making it possible to initiate a reflection on the local economic impact of artistic activities.